Investigation of deaths related to methyl alcohol intoxication in İzmir: A 5-year retrospective study - Ferhat Turgut Tuncez; Gulci̇n Tasci; Ismai̇l Ozgur Can; Mehmet Tokdemir (Medicine Science, 2023)
Methyl alcohol consumption results in serious poisoning symptoms and even causes death, so it is not used in legal alcoholic beverages. We aimed to examine deaths due to methyl alcohol intoxication in our region through forensic autopsies performed in İzmir-Turkey to compare these data with international studies. A total of 13,701 autopsies performed between 2016-2021 were scanned retrospectively. 214 cases in which the exact cause of death was methanol intoxication were included in the study. All the cases were analyzed in terms of age, gender, date of death, place of death, length of hospitalization, methanol levels detected in blood and the vitreous humor, ethanol presence in blood, and pathological findings. The ratio of autopsies of the exact cause of death of methanol poisoning to total autopsies is 1.56%. Of these cases, 94.9% were male and 5.1% were female. The age range was 25–80 years, with a mean age of 53.4. According to the age distributions, the highest rate was 39.3% in the sixth decade. The highest number of cases was 129 (60.3%) in 2020. In the analysis of blood methanol levels, the concentration was found to be in the range of 0-642 mg/dl and the mean was 178 mg/dl. During the COVID-19 pandemic, there has been a significant increase in methanol poisoning cases associated with the economic and social problems experienced in Turkey. Our study showed that methanol poisoning deaths are especially common in men aged 50-60 years so this group is at higher risk of methanol poisoning. [Med-Science 2023; 12(4.000): 1324-30]